2020
DOI: 10.1371/journal.pone.0240184
|View full text |Cite
|
Sign up to set email alerts
|

Are quantitative features of lung nodules reproducible at different CT acquisition and reconstruction parameters?

Abstract: Consistency and duplicability in Computed Tomography (CT) output is essential to quantitative imaging for lung cancer detection and monitoring. This study of CT-detected lung nodules investigated the reproducibility of volume-, density-, and texture-based features (outcome variables) over routine ranges of radiation dose, reconstruction kernel, and slice thickness. CT raw data of 23 nodules were reconstructed using 320 acquisition/reconstruction conditions (combinations of 4 doses, 10 kernels, and 8 thicknesse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
(70 reference statements)
2
15
0
Order By: Relevance
“…We used stratified random sampling to balance the covariates. In feature selection, A few issues regarding the stability and reproducibility of the radiomics features have been raised in recent years (31)(32)(33). Multiple parameter changes (e.g., slice thickness) in general produce greater measurement errors.…”
Section: Discussionmentioning
confidence: 99%
“…We used stratified random sampling to balance the covariates. In feature selection, A few issues regarding the stability and reproducibility of the radiomics features have been raised in recent years (31)(32)(33). Multiple parameter changes (e.g., slice thickness) in general produce greater measurement errors.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate this effect, Park et al demonstrated that CT feature reproducibility can be improved by using a CNN-based super resolution algorithm [31] . For CT studies, Erdal et al pointed out that a slice thickness of 2 mm leads to the most accurate shape features [32] . It remains unclear if radiomic features extracted from images acquired under different conditions also lead to different conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…Also in CT studies, contours delineated by different clinicians impacted the prognostic value of radiomic features. For head and neck cancer, in one PET and one MR study features were found to be very sensitive to differences in tumor delineation [32] , [33] , [37] , [44] . Overall, semi-automated and automated algorithms produced more stable results.…”
Section: Resultsmentioning
confidence: 99%
“…An important aspect is the CTTA reproducibility related to the influence of CT acquisition parameters (e.g., level of radiation dose, slice thickness, reconstruction algorithms) that can affect results and standardization among different Diagnostics 2021, 11, 1000 2 of 10 studies [8][9][10]. This aspect is gaining interest, as shown by Erdal et al [11] who demonstrated that slice thickness influenced reproducibility of radiomic features in lung nodules, and Prezzi et al [12] who showed the influence of iterative reconstruction (IR) algorithm versus traditional filtered back projection (FBP) on radiomics quantification in twenty-eight datasets of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%